The Level of Altruistic Action Based on the Dimension of Mutual Cooperation in Strengthening the Profile of Pancasila Students Grade X in High School - Destanika Dhiffa Ralianti; Adi Atmoko; Diniy Hidayatur Rahman (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Altruistic action is the act of helping others and the desire to do good without expecting anything in return. Altruistic action is the act of helping others and the desire to do good without regard for reward. This study aims to describe the level of altruistic action among tenth-grade students at Nurul Huda Senior High School in relation to the implementation of the independent curriculum, with a focus on the dimension of cooperation. The research design employed a quantitative approach, utilizing a survey. The population of tenth-grade students was 160 students, and the sample size was 111 students. The sampling technique was proportional random sampling. Data collection used a questionnaire. Data analysis employed descriptive statistical methods, presented as percentages. The results showed that the overall level of altruistic action fell into three categories: high (21%), medium (79%), and low (0%). The level of altruistic action in the aspect of cooperation was categorized as high (14%), medium (85%), and low (1%). The element of sharing was categorized as high (37%), medium (63%), and low (0%). The aspect of helping was categorized as high (72%), medium (28%), and low (0%). Based on these data, it was concluded that the level of altruistic action of tenth-grade students tended to be in the moderate category. Keywords: altruistic actions, cooperation, class X students